Disolución Societaria De Una Empresa Constructora Y Propuesta De Sostenimiento De Desempeño Y Calidad Del Trabajo - Beltram, Verónica (European Scientific Journal, ESJ, 2016)
In the analyzed work group there was a breakup between the partners. As result of this disolution, significant shortcomings were produced in the working structure of the organization, namely: 1. Disruption of the group members. 2. Disorientation regarding the direction and planned goals of the business unit. 3. Endangered mission and vision of the enterprise. 4. Crisis of current values. 5. Enhancement of the lack of clear and shared objectives and shared functions and tasks of each member, which that already existed. 6. Some vacancies were filled and others resulted obsolete. 7. Some tasks were neglected, seriously hindering the achievement of the objectives and the quality of customer service delivery. 8. Intensification of informal communication, which in many situations misrepresent the true reality of the situation presented, seriously impending normal decision making for their solution. 9. All decisions focus on the principal director, producing delays in decisions.